IMPLEMENTING BLOOM’S TAXONOMY IN THE ENGLISH CURRICULUM UNDER MERDEKA BELAJAR PROGRAM - Edi, Syamsi; Iswandini, Iswandini; Andriani, Novi; Aryaningsih, Nur (University of Kuningan, 2024)
Education in Indonesia in the 5.0 era utilizes the MBKM English Education Curriculum, which is a modification of the 2013 English Education Curriculum. According to the 2019 PISA survey, Indonesia ranked 74th out of 79, indicating that the cognitive development of Indonesian children remains relatively low. The